2023
DOI: 10.1007/s11356-023-26335-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of meteorological factors and extreme weather on daily outpatient visits for conjunctivitis from 2013 to 2020: a time-series study in Urumqi, China

Abstract: Conjunctivitis is a common multifactorial inflammatory ocular surface disease characterized by symptoms such as congestion, edema, and increased secretion of conjunctival tissue, and the potential effects of meteorological factors as well as extreme meteorological factors on conjunctivitis and their lagging effects have not been fully evaluated. We obtained the electronic case information of 59,731 outpatients with conjunctivitis from the Ophthalmology Department of the First Affiliated Hospital of Xinjiang Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…A further increase in visits was registered at lower levels of RH. However, only a slight effect of HR was shown in the multiple meteorological factor model (RR = 1.021-1.025) [8]. Furthermore, the study results suggested that a low RH was significantly associated with the risk of conjunctivitis during the warm season.…”
Section: Allergic Diseases and Rh Influencing Effectsmentioning
confidence: 64%
See 2 more Smart Citations
“…A further increase in visits was registered at lower levels of RH. However, only a slight effect of HR was shown in the multiple meteorological factor model (RR = 1.021-1.025) [8]. Furthermore, the study results suggested that a low RH was significantly associated with the risk of conjunctivitis during the warm season.…”
Section: Allergic Diseases and Rh Influencing Effectsmentioning
confidence: 64%
“…In a large Chinese population, extremely low levels of atmospheric pressure andRH, as well as extreme levels of temperature, were significantly associated with an increased risk of outpatient visits for conjunctivitis. In the same study, high-speed wind was a protective factor [8]. The negative impact of dry air on the conjunctival mucosa is due to multiple mechanisms, such as the impairment of the lacrimal film due to water evaporation and the reduction of its thickness.…”
Section: Rh Alteration and Its Direct Effects On Healthmentioning
confidence: 78%
See 1 more Smart Citation
“…Demographic and environmental factors, area, and admission time were adjusted for in logistic regression models on the basis of the significance of bivariate association and previous knowledge (Supplementary Tables S2 and S3). Estimated changes in tested pathogens and pneumonia severity were evaluated given a 10-μg/ m 3 increment in PM2.5, PM10, SO 2 , NO 2 , and O 3 -8h exposure [21], given a 1-mg/m 3 increment in CO exposure [22], given a 10% increment in RH exposure [23], and given a 1°C increment in temperature. While variables and models of DLNM were shown in Supplementary Text S4.…”
Section: Discussionmentioning
confidence: 99%